MENCIPTAKAN PEMBELAJARAN MATEMATIKA YANG KREATIF DAN MENYENANGKAN - Rahmi, Rahmi (Jurnal Pelangi : Research of Education and Development, 2013)
The general puposes of experiencing math subject to elementary and middle school students are; first preparing the students to face the changing of real life through the thinking rehearsal based on the effective, effisien, honesty, critical, rationale, and logical way of thinking, and second, preparing the students to apply the mental principle of math in their daily life and as basic in learning other disciplines. Regarding to the importance of learning this subject, teacher of math should be able to create an effective teaching learning process to stimulate and to rise students enthusiasm in learning match. One of the strategy that can increase students desire in learning math is PAILKEM (Pembelajaran Aktif, Inovatif, Lingkungan, Kreatif, Efektif, dan Menarik). There is an interactive dialoque between teacher students and students-students, during teaching-learning process.This creates a condusive situation in wich students feel free to discuss their problems in learning math to their teachers and their classmates. At the end, through this strategy, students can increase their ability in learning and it is hoped that teaching learning process will be done in optimal achievement.